Diseño de un plan de marketing social orientado a la prevención del cáncer de mama para la sociedad de lucha contra el cáncer Solca núcleo de Quito, ubicado en la provincia de Pichincha. - Granja Abril, Evelyn Cristina (2013)
The present research is aimed at “Sociedad de Lucha Contra el Cancer” SOLCA Quito, aims to design a social marketing plan aimed at the prevention of breast cancer which is the design of programs designed to generate acceptance of preventing this catastrophic disease, influencing the voluntary behavior of each person in order to improve their personal welfare and especially the health of society, in this research we analyze the plan in five chapters contain the following.